Weight gain and carrageenan content of Kappaphycus alvarezii (Rhodophyta, Solierisceae) polycultured with Sargassum polycystum (Paeophyta, Sargassaceae). (April 2019) - Syamsuddin, R; Abustang; Ruslaini; Tuwo, A; Aswar, N R
Abstract: The objectives of this study were to analyse the weight gain and carrageenan content of the seaweed Kappaphycus alvarezii polycultured with Sargassum polycystum seed. The study was conducted in the coastal waters of Aeng Batu-Batu Village, Takalar Regency, South Sulawesi, Indonesia from July 13, 2016 to September 7, 2016. A Complete Randomized Design (CRD) was applied with 4 treatments and 3 replicates. The treatments were a control ( K . alvarezii with no S . polycystum ); the combination of 25 g K . alvarezii with 25 g S . polycystum ; 25 g K . alvarezii with 30 g S. polycystum ; and 25 g K . alvarezii with 35 g S. polycystum. High weight gain and carrageenan content of K . alvarezii in the presence of S . polycystum could be due to the shading effect of thallus morphology and the chemical content of S . polycystum that might protect the thallus of K . alvarezii from herbivorous animals, biofouling, and UV radiation. The antibiotic compounds, hormones, and phlorotannins content of S . polycystum may synergistically protect the red seaweed from ice-ice bacteria while promoting growth and carrageenan synthesis.